“It Adds to The Stress of the Body”: Community health needs of a state-recognized Native American tribe in the United States - Buxbaum , Lauren; Hubbard, Hollis; Liddell, Jessica (Journal of Ethnic and Cultural Studies, 2023)
While many of the health disparities, brought on by the cruelties of settler colonization, that affect Native American and Alaskan Native communities and individuals at high rates have been documented, the health risks impacting non-federally recognized tribes are less explored. In this manuscript, we explore the challenges non-recognized tribes face and how without Tribal sovereignty, autonomy, and resources, it is more difficult for non-recognized tribes to provide care and resources for the members of their communities. This study took place in the Gulf South regions of the United States, where there are environmental factors pertaining to industry, global warming, environmental racism, and rurality that further impact the quality of life and rates of cancer, respiratory illness, and reproductive health issues in the Native American communities that live there. In addition, tribes without federal recognition have increased challenges in addressing the lack of access to health equity and may not have the health resources or programming available to them that exist for federally recognized tribes. To explore these topics, a qualitative description methodology was used to conduct 31 semi-structured interviews with women from a state-recognized Native American tribe in the Gulf South to understand their healthcare experiences and concerns. Participants in this study described: high rates of cancer, vehicle accidents or collisions common, barriers to exercising, physical injuries common, chronic illnesses common in the community, loss of family members, and physical violence. These findings indicate that state-recognized tribal members may need increased, improved, and culturally contextualized healthcare programs within their communities, in addition to full recognition of their tribal sovereignty rights. This study begins to address important gaps in the research exploring the full scope of the health risks and challenges affecting non-federally recognized tribal members, while also highlighting their resilience in the face of settler colonialism.